Proposing the value of Amanah as the foundation of Zakah organizational culture - Tjiptohadi Sawarjuwono, Rahmad Hakim,; Djalaluddin, Ahmad (Opción, 2019)
This study aims to explore in-depth analysis on the formulation of Amānah value as Islamic organizational culture for zakah institution and its operationalization for zakah institution via comparative qualitative research methods. As a result, the indicator of accountability can be seen by zakah institution’s concern to financial accountability, process accountability, and so on. This research concluded that there are five dimensions related to the formulation of Amānah as the foundation of Islamic organizational culture for zakah institution, namely: mentality, capability, accountability, professionalism, and an appropriate disbursement.